WACANA SUFISTIK : TASAWUF FALSAFI DI NUSANTARA ABAD XVII M: ANALISIS HISTORIS DAN FILOSOFIS - Syafwan Rozi (Islam Realitas: Journal of Islamic and Social Studies, 2017)
Sufistict discourse of Sufism philosophy has grown rapidly to accompany the development of Islam in the period of growth in the archipelago. Seen from the source or network, in the 17th century AD it understood to be brought by the Sufi clerics or nomads who came from Persia and India, although the period appears haramain network is considered as a counter that ultimately criticize the ideology of philosophical Sufism that has developed before. The ideology of philosophical Sufism which developed in the archipelago in terms of the essence of the teachings comes from the philosophical Sufi mursia Ibn 'Arabi received by the archipelago of the archipelago through the followers of Ibn'Arabi or learned from his works which are encountered when wandering the middle queue - persia to study. Hamzah Fansuri and Syamsuddin Sumaterani as representenatasi of wujudiyyah in the archipelago is very stressed to maintain the concept of monotheism in an original and really crowded God. Hamzah especially emphasizes the stages of la ta'ayyun as a pure divine element. While Syamsuddin emphasize to his followers to understand al-muwahhidin al-shiddiqin, not equating anatara God with nature but understood by the logic of thinking that the form of nature is majazi or shadow of the form of God. With this understanding Syamsuddin has first clarified. Wacana sufistik tasawuf falsafi telah berkembang pesat mengiringi perkembangan Islam pada masa pertumbuhan di Nusantara. Dilihat dari sumber atau jaringannya, pada abad ke-17 M, paham tersebut dapat dikatakan dibawa oleh ulama atau pengembara sufi yang datang dari Persia dan India, walaupun kurun itu muncul jaringan Haramain dianggap sebagi tandingan yang akhirnya mengkritik paham tasawuf falsafi yang telah berkembang sebelumnya. Paham tasawuf falsafi yang berkembang di Nusantara dari segi esensi ajaran berasal dari sufi filosofis mursia Ibn’ Arabi yang diterima ulama Nusantara melalui pengikut-pengikut Ibn’Arabi atau dipelajarai dari karya-karyanya yang ditemui ketika mengembara ke timut tengah – persia untuk menuntut ilmu. Hamzah Fansuri dan Syamsuddin Sumaterani sebagai representasi dari paham wujudiyyah di Nusantara sangat menekankan untuk memahani konsep tauhid secara orisinil dan benar-benar mengesakan Tuhan. Khususnya Hamzah menekanan sekali tahapan la ta’ayyun sebagai unsur ketuhanan yang murni. Sedangkan Syamsuddin menekankan kepada pengikutnya untuk berpaham al-muwahhidin al-shiddiqin, tidak menyamakan anatara Tuhan dengan alam tapi dipahami dengan logika berfikir bahwa wujud alam adalah majazi atau bayangan dari wujud Tuhan. Dengan paham ini Syamsuddin telah terlebih dahulu mengklarifikasi.